Popular Attacks on IoT Layers and its Countermeasures, Security Requirements and Open Issues - E.Sandhya, Dr. Annapurani (International Journal of Advanced Science and Technology, 2020)
The interconnection of collaborative devices through internet as an interactivemedium is the basis forIoT. The advent of IoT makes our lives smarter and better.At the flipside, IoT is still emerging technology and due to constrained environment; it is prone to several attacks, especially Distributed Denial of Service (DDoS) attack tops in list.We present a taxonomy that covers all possible categories of attacks that occur in IoT.The paper exposes popular attacks layer wise in IoT reference model.Also, the paper covers security requirements and measuresto tackle the threats in IoT environment.